Jeden falszywy ruch - Coben, Harlan, 1962-; Grabowski, Andrzej (Warszawa : Wydawn. Aleksandra i Andrzej Kurylowicz/Albatros, 2004)
Polish translation of "One false move". A detective mystery novel. Set in New York city about a women's basketball team.
Translation of: One false move.
Keywords: Bolitar, Myron (Fictitious character) -- Fiction; Sports agents -- Fiction; Women basketball players -- Fiction; New York (N.Y.) -- Fiction